DKK1 expression is suppressed by miR-9 during induced dopaminergic differentiation of human trabecular meshwork mesenchymal stem cells. (10th August 2019) - Mirfazeli, Elham Sadat; Arefian, Ehsan; Nadri, Samad; Rezazadeh Valojerdi, Rezvan; Kehtari, Mousa; Zeynali, Bahman
Highlights: Wnt/β-catenin pathway is activated during dopaminergic differentiation period. DKK1 expression is reduced in the process of dopaminergic neuron differentiation. miR-9 negatively regulates DKK1 expression through targeting 3′UTR regulatory region. Abstract: Wnt/β-catenin pathway has been recently identified as one of the key players in dopaminergic (DA) neuron differentiation. DKK1, the potent inhibitor of the Wnt/β-catenin pathway, is expressed in a precisely controlled manner in ventral midbrain during brain development, however the molecular mechanism underlying this regulation is still unknown. Here we show that human trabecular meshwork mesenchymal stem cells (TM-MSCs) can be used as an efficient tool for in vitro differentiation of DA neurons. After differentiating TM-MSCs to DA neuron-like cells, β-catenin protein accumulation was increased in the nucleus, indicating the increased activity of Wnt/β-catenin pathway in the time-window of DA differentiation. Interestingly, DKK1 transcript level was reduced dramatically after DA induction in TM-MSCs which was accompanied by an increase in the in silico -predicted MIR9 and MIR101 levels. Measuring DKK1 expression level after overexpressing either MIR9 or MIR101 and performing luciferase assay alongside, revealed that both miR-9 and miR-101 suppress DKK1 expression and that miR-9 exerts a direct inhibitory effect on 3′UTR regulatory region. Therefore miR-9 and miR-101 might explain, at least in part, the underlying regulatory mechanism of DKK1 reduction and resulting Wnt/β-catenin pathway activation during DA neuron differentiation process.